KONSEP PENDIDIKAN KI HADJAR DEWANTARA TERHADAP PEMBENTUKAN PERILAKU MORAL SISWA DI ERA SOCIETY 5.0 - Fitria Ayu Nur Azizah (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2024)
Ki Hadjar Dewantara's educational concept is educational concept that provides free and independent teaching and learning that is tailored to the needs of each student. In this era of humans living side by side and inseparable from the role of developing technology, it makes it easier for individuals to search for and access incoming and even developing information and culture. The purpose of this writing is to provide and describe new information and knowledge regarding educational concepts taught by Ki Hadjar Dewantara in helping to shape students' moral behavior in the modern era or society 5.0. The method used in this writing is to use qualitative research using descriptive analysis techniques of literature review to describe phenomena that are ongoing/have occurred. Based on the results of a literature review conducted from several literary sources used in obtaining knowledge and information regarding Ki Hadjar Dewantara's educational concept in helping to shape students' moral behavior is by conducting education and teaching using the among system for students with educators understanding the 3 concepts of civil service guidelines, namely Ing Ngarsa Sung Tuladha, Ing Madyo Mangun Karsa, and Tut Wuri Handayani. The formation of students' moral behavior also needs to involve the role of the Three Education Centers synergistically, so that they can form strong moral behavior in the era of society 5.0.